ALAN SILLITOE'S WORKING-CLASS FICTION - Shivani Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
In a broad sense, the term "fiction" refers to any fabricated literary narrative, regardless of its form. Take, as an illustration, Gulliver's Travels by Jonathan Swift. In a more specific sense, the term "fiction" refers to any literary tale, typically written in prose (and this includes short stories), which may be autobiographical, historical, or based on made-up events. However, "fiction" is short for "novel." The term "working-class fiction" can be used to refer to a certain type of historical or modern reality. It can be considered a form of truth. This body of fiction is partly set in the past (as is the case with its representation in Dickens's Hard Times) and partly set in the present (as is the case with Alan Sillitoe's classic novel Saturday Night and Sunday Evening (1958)), makes use of imitation, imagination, and fiction or invention. It is a fictitious portrayal of a real-world debate of some kind. It is a representation of the verbal actions, reporting, describing, and referring done by members of the working class. The majority of contemporary critics of prose fiction, regardless of their ideological orientation, make a significant distinction between the fictional scenes, persons, events, and dialogue that a narrator reports or describes and the narrator's own assertions about the world, about human life, or about the human situation. The central or controlling generalizations of the latter sort are referred to as the theme or thesis of a piece of work.